COVID-19 related multisystem inflammatory syndrome in children: a case series from a tertiary care centre in Western Uttar Pradesh - Upadhyay, Shobhit; Dayal, Rajeshwar; Nayak, Madhu (International Journal of Contemporary Pediatrics, 2025)
A minority of children infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) present with multisystem inflammatory syndrome in children (MIS-C), usually 2 to 4 weeks post-infection, the pathophysiology of which is still unclear. MIS-C referred to overlapping clinical features of KD, TSS, and macrophage activation syndrome with acute abdominal presentations upon admission. This is a case series of 5 children which includes COVID-19 serology positive patients admitted to Sarojini Naidu medical college, Agra, Uttar Pradesh from May 2020 to January 2022, who met the world health organization (WHO) case definition of MIS-C. The most common presenting symptoms of MIS-C patients at our hospital were fever (100%), reduced oral intake (100%), conjunctival hyperemia (100%), rash (100%), abdominal pain (80%), diarrhea (60%) and, vomiting (40%). All MIS-C patients displayed hyper inflammation, abnormal coagulation profiles, and elevated C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), and ferritin levels. High B-type natriuretic peptide (proBNP) and troponin levels were detected in 100% and 80% of the patients respectively. Two patients had ejection fractions (EF)<55% on echocardiography, indicating systolic ventricular dysfunction (case 4 and 5) with Mitral regurgitation was found in case 4 only. Broad-spectrum antibiotics, intravenous (IV) steroids and aspirin were administered to the all patients as per the ministry of health and family welfare guidelines for MIS-C. As this condition has severe effects on major systems, awareness among pediatricians is required for timely evaluation and treatment to prevent morbidity and mortality associated with MIS-C.